Hubungan dua hala Malaysia-Singapura: Transformasi dalam kepimpinan dalam menghadapi cabaran di era Abdullah dan Najib - Khalifa Omar, Abdullah (2014)
The purpose of this thesis is to study the leadership of Abdullah and Najib in bringing Malaysia-Singapore relations towards the better prospect after the era of Mahathir. The aim of this thesis is to study the changes in the foreign policy of Malaysia-Singapore together with their leadership style. In addition to that, I will also examined the relationship between leadership characteristics and the changes of countries relationship. Besides that, i will also examines the changes that have been brought by Abdullah and Najib in the implemention of foreign relations with Singapore in which I will covered the year of 2003-2009 (Abdullah’s era) and 2009-2014 (Najib’s era). For this purpose, information is gathered from various sources, whether related to economy, politic or any other; so that they are consistent with the requirement of the study.